Dimensioning and analisys of energy systems for irrigation in farms in Minas Gerais state (Research, Society and Development, 2017)
This study consists of an analyzing from the energy, economic and environmental points of view the acionament systems used for irrigation in agricultural areas in the state of Minas Gerais (MG). By performing analysis of economic feasibility and environmental impacts of each form of drive used in systems for irrigation, will be evaluated the most appropriate primary drive for the case study evaluated in an agricultural area in Minas Gerais, considering the drive motor pump linked directly in the power grid, diesel motor and photovoltaic energy, both on grid and off grid. It will be seen that the use of the electrical network to trigger the irrigation system’s motopump set is the most indicated primary drive for the realized case study, because it presents total annual costs much lower than the others, and the fotovoltaic systems are the most beneficial ones in relation to environmental impacts, because their use doesn’t result in environmental pollution. In relation to the use of the diesel engine, the price of the diesel renders its use very expensive, besides generating high levels of CO2 into the atmosphere.